Modern Democracy: Issues in Theory and Practice - Dr. Rehana Saeed Hashmi (Journal of Political Studies, 2018)
Considering Democracy as the best form of government is self-evidently true. The meaning of democracy is rooted in the concept of common people being master of their affairs. In the words of Robert Dahl “democracy prevents despotism”. (Dahl, 2000). Today democracy is being promoted, propagated and practiced across globe from developed nations of Europe and America to the developing countries of Africa and Asia, it is prevailing everywhere. Despite it’s widely acceptance, the question is whether the practices of modern democracy are up to its definitions. This research undertakes the task to find out the answer to this emerging query. The research includes the theoretical framework of democracy in detail and has explained the complicated trends and structures in modern democracy such as media and global economy and how they are marginalizing the role of common man and killing the real spirit of democracy i.e. rule by the consent of the ruled. The researcher has evaluated the democratic practices of America and Europe as they are considered the greatest democracies of the world. The research has analyzed that to what extent their political system is democratic. Furthermore, some features of developing democracies are also summed up as well. After the evaluation, it is found that due to political maneuvering and economic competition the welfare of the masses is compromised.